Chapter: Introduction - Field Experiments - Anya Samek; John A. List (Edward Elgar Publishing, 2018)
This research review discusses the most critical and influential articles that utilise field experimentation to answer questions of economic importance. Field experiments have gained popularity in recent years, allowing researchers to infer causal effects of different market environments, policies and interventions. The articles analysed here provide insights into market functioning and individual and group decision-making across a wide range of domains, including marketplace transactions, labor decisions, charitable giving, financial planning, and education and health-related decision-making. This research review will be an important resource for students new to the methodology and applications of field experiments and academics alike.
English
Keywords: market environments; decision-making; economic importance; Field experimentation; marketplace transactions